The Importance of The Integrated Security System For Critical Infrastructure Operation And Safety - Jarosław NAPIÓRKOWSKI (Communications of International Proceedings, 2021)
The paper is focused on theoretical and practical aspects concerning the role of the IT elements of the integrated security system in the process of maintaining nor increasing the level of security related to the critical infrastructure (CI). The role of this system is to increase the effectiveness of detecting, counteracting, and neutralizing the effects of cyber hazards for the CI. Authors refer to the tasks of the units that are responsible for the cybersecurity of the CI. These tasks are arranged around the three dimensions: technology, organization, and processes. They are considered to be a substantial part of the processes of maintaining the critical infrastructure operations continuity, eliminating a single point of failure (SPOF), separating critical infrastructure elements from the outside world, and raising awareness.
Keywords: Critical Infrastructure; National Risk Management; National Security; Security System.